Urinary Levoglucosan as a Biomarker for Wood Smoke: Results of Human Exposure Studies - Bergauff, Megan A. (2009)
Urinary levoglucosan was investigated as a potential biomarker for wood smoke exposure in two different controlled experimental settings. Nine subjects were exposed to smoke from a campfire in a controlled setting and four were exposed to smoke from an older model wood stove. All subjects were asked to provide urine samples before and after exposure, and to wear personal PM(2.5) monitors during the exposure. Urinary levoglucosan measurements from both studies showed no consistent response to the smoke exposure. A third experiment was conducted to assess the contribution of dietary factors to urinary levoglucosan levels. Nine subjects were asked to consume caramel and provide urine samples before and after consumption. Urinary levoglucosan levels increased within 2 hours of caramel consumption and returned to pre-exposure levels within 24 hours. These studies suggest that diet is a major factor in determining urinary levoglucosan levels and recent dietary history needs to be taken into account for future work involving levoglucosan as a biomarker of wood smoke exposure.